Corporate governance mechanisms and dividend decisions in emerging markets: Insights from India - Monika, Monika; Qamruzzaman, Md.; Kler, Rajnish (Edelweiss Applied Science and Technology, 2025)
This study examines the interplay between board compensation, audit committee independence, and dividend policies among Indian firms. Drawing on agency theory and corporate governance frameworks, it investigates how executive compensation structures and audit committee characteristics influence dividend decisions, using a sample of 426 non-financial firms listed on the Bombay Stock Exchange from 2012 to 2023. Employing advanced econometric techniques, including Tobit, Probit, and Generalized Method of Moments (GMM), the research provides robust insights into governance mechanisms. Key findings reveal a positive association between executive compensation and dividend payouts, suggesting that well-structured pay packages align managerial incentives with shareholder interests. Audit committee independence also demonstrates a significant positive impact on dividend policies, emphasizing its role in enhancing financial transparency and mitigating agency conflicts. The study further identifies gender diversity and board size as critical determinants of dividend decisions, while CEO duality emerges as a negative influencer. By addressing gaps in existing literature on emerging markets, this research underscores the need for strategic governance reforms. It advocates for effective compensation frameworks and independent audit committees to bolster transparency and protect minority shareholders. The findings offer actionable insights for policymakers, regulators, and corporate leaders striving to improve governance practices and align managerial actions with shareholder value creation. This study also contributes to the broader discourse on corporate governance by highlighting the unique dynamics within the Indian regulatory and economic landscape.